Post-weaning Exposure to High-Fat Diet Induces Kidney Lipid Accumulation and Function Impairment in Adult Rats - Muller, Cynthia R.; Leite, Ana Paula O.; Yokota, Rodrigo; Pereira, Renata O.; Americo, Anna Laura V.; Nascimento, Nilberto R. F.; Evangelista, Fabiana S.; Farah, Vera; Fonteles, Manasses C.; Fiorino, Patricia (Frontiers in Nutrition, 2019)
Aim: We investigated the renal lipotoxicity in adult rats exposed to high-fat diet since post-weaning. Main Methods: Male Wistar rats were divided into two groups: ND (normal diet; n=10) and HD (high fat diet; n=10). The high fat diet was introduced post weaned and animals were followed for 8 weeks. Key Findings: HD group did not change body weight gain even though food consumption has decreased with no changes in caloric consumption. The HD group showed glucose intolerance and insulin resistance. The glomerular filtration rate was decreased in vivo (ND: 2.8±1.01; HD: 1.1±0.14 ml/min) and in the isolated perfusion method (34% of decrease). Renal histological analysis showed a retraction in glomeruli and an increase in kidney lipid deposition (ND: 1.5±0.17 HD: 5.9±0.06%). Furthermore, the high fat diet consumption increased the pro-inflammatory cytokines IL-6 (ND: 1276±203; HD: 1982±47 pg/mL/mg) and IL-1b (ND: 97±12 HD: 133±5 pg/mL/mg) without changing anti-inflammatory cytokine IL-10. Significance: In our animal model, the kidney lipid accumulation can probably be the main trigger for kidney function loss and a risk factor for the development of more advanced stages of CKD. Our study provides evidence that high-fat diet consumption leads to renal lipotoxicity and important intra renal alterations that is strongly associated with the glomeruli retraction that could be determined by mesangial cell contraction. These alterations observed in kidney function could be associated with an increase risk to advanced CKD in adulthood suggesting that reduction of high-fat ingestion during early period of life has prevents metabolic disturbances and renal lipotoxicity.